Optimisation of a simultaneous saccharification and fermentation process for use with steam pretreated sweet sorghum bagasse - Dreyer, Casper Becker (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.